2008
DOI: 10.1243/09544100jaero261
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive moving mesh method with application to non-stationary hypersonic flows in the atmosphere

Abstract: A numerical algorithm based on a shock-capturing scheme on adaptive moving meshes is described. Three-dimensional dynamical adaptive meshes are generated as the result of solving a variational problem. The governing equations are solved in a moving coordinate system therefore the method does not require any interpolation of the solution from one mesh onto another one. The developed algorithm can efficiently be used for the simulation of non-stationary supersonic flows in the atmosphere. As an example, it is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Wave drag research is closely related to high-speed gas dynamics. This approach has been utilized to study the hypersonic displacement, with the corresponding complex wave pattern, of the Tunguska meteorite through the Earth's atmosphere until its fall on central Siberia [80]. And shock wave research has also found interesting applications in industrial areas, out of aerospace, such as medicine, material processing, or micro-electronics [81].…”
Section: Aerodynamic Analysis and Applicationsmentioning
confidence: 99%
“…Wave drag research is closely related to high-speed gas dynamics. This approach has been utilized to study the hypersonic displacement, with the corresponding complex wave pattern, of the Tunguska meteorite through the Earth's atmosphere until its fall on central Siberia [80]. And shock wave research has also found interesting applications in industrial areas, out of aerospace, such as medicine, material processing, or micro-electronics [81].…”
Section: Aerodynamic Analysis and Applicationsmentioning
confidence: 99%